Exploring Self-Disclosure Trends Among Students: A Descriptive Study - Isnaeni Solehah; Nandang Rusmana; Dadang Sudrajat (Journal of Education and Counseling (JECO), 2024)
This study aims to describe the trend of self-disclosure owned by students. By using a quantitative approach and descriptive method and taking a comprehensive sample. The research participants consisted of 830 students in Indonesia, consisting of 322 male students and 508 female students. The measurement tool used was the Jourard Self-Disclosure Questionnaire (JSDQ). The results showed that 60% of students tended to favor offline self-disclosure, while 39.4% preferred online self-disclosure.